The inclusion of the other in ourselves: reception and comprehension of refugees in Portugal - Prata Gomes, Miguel (2017)
The intensification of different types of migration movements during the last decades is an expression of growing interconnections at the global level. The so called ‘refugee crisis’ is the most visible sign of this intensification. It currently challenges societies to rethink the processes of integrating those fleeing from humanitarian crises and wars. Portuguese civil society has pioneered the creation of a Refugee Support Platform, aimed to address the challenges associated with the arrival of refugee families. Within this platform, an e-learning course was created to help institutions and host families prepare for this task. In the article we first describe this course, focusing our analysis on the relevance of this initiative for institutions, families, and private citizens that wish to welcome refugees in Portugal. We then briefly reflect on the literature pertaining to intercultural dialogue and social tensions. In the final section we analyse the voices of those who attended the course. We conclude with an analysis of the contents of the course modules and the participation of the trainees as a contribution to their self-transformation.